Diagnóstico de la calidad microbiológica, fisicoquímica y mecánica de carne bovina expendida en el cantón Flavio Alfaro - Japón Salazar, Johanna Sofía (2024)
The objective of this research was to evaluate the microbiological, physicochemical, mechanical and hygienic-sanitary aspects of beef marketed in the Flavio Alfaro canton. A non-experimental, cross-sectional and descriptive design was used, studying 6 thirds, chosen by convenience. Analyses of mesophilic aerobes, Escherichia coli, Staphylococcus aureus and Salmonella according to NTE INEN 1338 (2016) for meat and meat products and physicochemical tests for pH, titratable acidity, organochlorines and organophosphates were carried out. The texture profile of the meat was evaluated by means of hardness, elasticity and cohesiveness. Meat from the best establishment in microbiological quality was tested for organochlorine and organophosphorus compounds. The hygienic-sanitary conditions of the establishments were evaluated with a checklist according to NTE INEN 2687 (2013) for healthy markets. The results revealed that the meat from the 6 establishments did not meet the microbiological requirements. The pH (6.37 and 6.88), was outside the limits established by NTE INEN 783 (1985), but in accordance with NTE INEN 2346 (2010). The titratable acidity (0.90% and 1.80%) did not comply with the latter standard. With the exception of the meat from third 3 and 4, all of them had an undesirable texture profile. None of the establishments complied with the facilities, services and hygiene requirements of NTE INEN 2687 (2013). Tertiary 3 presented an average of ˂0.0002 mg/Kg for organochlorine compounds and ˂0.01 mg/Kg for organophosphates, being within the limits according to the Codex Alimentarius.